1999
DOI: 10.1084/jem.189.3.575
|View full text |Cite
|
Sign up to set email alerts
|

Bad Can Act as a Key Regulator of  T Cell Apoptosis and T Cell Development

Abstract: Bad is a distant relative of Bcl-2 and acts to promote cell death. Here, we show that Bad expression levels are greatly increased in thymocytes during apoptosis. We generated bad transgenic mice to study the action of upregulated Bad expression on T cell apoptosis. The T cells from these mice are highly sensitive to apoptotic stimuli, including anti-CD95. The numbers of T cells are greatly depleted and the processes of T cell development and selection are perturbed. We show that the proapoptotic function of Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 52 publications
6
82
2
Order By: Relevance
“…However, a previous array study to find GRregulated genes in phytohaemaglutinin-stimulated peripheral blood mononuclear cells showed upregulation of STAT1 and BAD in agreement with our results (Galon et al, 2002). Although no direct regulation of BAD by GR has been shown previously, Gc-induced apoptosis in primary T cells in vivo and in vitro is associated with a significant upregulation of BAD (Mok et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…However, a previous array study to find GRregulated genes in phytohaemaglutinin-stimulated peripheral blood mononuclear cells showed upregulation of STAT1 and BAD in agreement with our results (Galon et al, 2002). Although no direct regulation of BAD by GR has been shown previously, Gc-induced apoptosis in primary T cells in vivo and in vitro is associated with a significant upregulation of BAD (Mok et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies of cell lines have shown that IL-7 can promote cell survival by inactivating Bad through its Akt/PKBdependent phosphorylation [31]. However, detailed analysis of F5 transgenic mice that over-express Bad, consequently inducing thymocyte apoptosis [32] (Supporting Information Fig. 4A), revealed no evidence of defects in naïve T-cell survival in vitro (Supporting Information Fig.…”
Section: Il-7 Signalling In Vivo Regulates Mitochondrial Homeostasismentioning
confidence: 95%
“…(F5Rag1 À/À Â C57BL/6J Ly5.1)F1 mice were used as controls throughout. These strains and F5 Rag1 À/À Bad huCD2 [32], Rag1 À/À , Il7r À/À and F5 Rag1 À/À mice were bred in a conventional colony free of pathogens at the NIMR, London. …”
mentioning
confidence: 99%
“…In particular, overexpression of the anti-apoptotic members of this family in B and T cells delays entry into S-phase [5][6][7] and accelerates withdrawal from the cell cycle [8,9]. In contrast, overexpression of pro-apoptotic members such as Bax or Bad in T cells of transgenic mice increases the number of cycling thymocytes, favouring entry into S-phase [6,10]. The ability of Bcl-2 to interfere with cell-cycle progression is not limited to lymphoid cells, but has also been observed in murine fibroblasts [7,11].…”
Section: Introductionmentioning
confidence: 99%